Adherence to International Guidelines in Antihypertensive Prescriptions among National Health Insurance Enrollees in a Tertiary Hospital Located in Abuja, Nigeria - Shedul, Grace Julcit; Eraga, Sylvester Okhuelegbe; Odili, Valentine Uche; Ojji, Dikejiunor Bevis (Indian Journal of Pharmacy Practice)
Background: Irrational prescription of antihypertensive drugs has become a major problem worldwide. The study aimed at investigating the conformity of antihypertensive prescriptions to current international guidelines among NHIS enrollees in a tertiary hospital and to determine the comorbidities among the patients. Materials and Methods: This was a descriptive and retrospective cross-sectional study. A total of 311 case notes of patients who accessed care from January 1st to December 31st, 2018 were retrieved from the Health Information Department of the Hospital. Information on antihypertensive drugs prescribed and their co-morbidities were retrieved. Results: Study participants mean age was 49.02 ± 9.16 with age groups of 40 – 59 and 20 – 39 years as the highest and lowest participants, respectively in the study population. Calcium channel blockers (32.44%) were the most prescribed of the antihypertensive drugs, followed by diuretics (13.93%). The majority (84.0%) of the study participants were on combined therapy. Amongst the combination therapies, the 2-drug therapy (28.97%) was most preferred. The commonly used combinations were CCB + ARB (92, 84.40%), CCB + ARB + Diuretic (30, 30.92% and CCB + ACEI + 2 Diuretics (22, 53.65%) for 2-, 3- and 4-drug, respectively. The common comorbidities found among the patients were diabetes mellitus followed by hypertensive heart disease then dyslipidaemia. Antihypertensive prescriptions conformed more with JNC 8 but partially to JNC 7 and ACC/AHA. Conclusion: Antihypertensive prescriptions among NHIS enrollees in the University of Abuja Teaching Hospital were in conformity with JNC 8 and adheres partially to other guidelines.
Keywords: Antihypertensives; Prescriptions; Conformity; International guidelines